PENERAPAN MODEL PROBLEM BASED LEARNING MATERI PEMISAHAN CAMPURAN UNTUK MENINGKATKAN KETERAMPILAN PROBLEM SOLVING MURID SMP - Risma, Maya Widya; Sudibyo, Elok (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to determine the improvement in problem-solving skills of junior high school students, the implementation of learning, and student responses after the application of the Problem Based Learning (PBL) model to the material on separating mixtures. The type of research used is pre-experimental design with a One Group Pretest–Posttest design. The subjects in this study were 30 students of class VIII-G of SMP Negeri 12 Gresik. The results of the study showed that there was a significant difference between the pretest and posttest scores of students after the Problem Based Learning (PBL) model was applied with a significance value of the paired sample t-test of Sig.<0.05. Based on the N-Gain analysis, it shows an increase in students' problem solving skills of 0.63 with a moderate category. The indicator with the highest average score is the Exploring and Understanding (EU) Indicator at 0.8 and the lowest average score is the Monitoring and Reflecting (MR) Indicator which has an N-Gain score of 0.3. The implementation of the learning carried out has been carried out in the very good category and has achieved an implementation percentage of 100%. In addition, student responses to the application of the Problem Based Learning (PBL) model showed a very positive response with a percentage of 94.17%, which indicates that this learning model can attract, motivate, and help students in understanding the material on separating mixtures. Based on these results, it can be concluded that the Problem Based Learning (PBL) model is effective in improving the problem solving skills of junior high school students. ABSTRAK Penelitian ini bertujuan untuk mengetahui peningkatan keterampilan problem solving murid SMP, keterlaksanaan pembelajaran, serta respons murid setelah diterapkannya model Problem Based Learning (PBL) pada materi pemisahan campuran. Jenis penelitian yang digunakan adalah pre-experimental design dengan rancangan One Group Pretest–Posttest. Subjek dalam penelitian ini merupakan murid kelas VIII-G SMP Negeri 12 Gresik dengan jumlah 30 murid. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan antara nilai pretest dan posttest murid setelah diterapkan model Problem Based Learning (PBL) dengan nilai signifikansi Uji paired sample t-test sebesar Sig.<0,05. Berdasarkan analisis N-Gain menunjukkan peningkatan keterampilan problem solving murid yaitu sebesar 0,63 dengan kategori sedang. Indikator dengan skor rata-rata tertinggi adalah Indikator Exploring and Understanding (EU) sebesar 0,8 dan skor rata-rata terendah terdapat pada Indikator Monitoring and Reflecting (MR) yang memiliki skor N-Gain sebesar 0,3. Keterlaksanaan pembelajaran yang dilakukan telah terlaksana dengan kategori sangat baik dan memperoleh persentase keterlaksanaan sebesar 100%. Selain itu, Respons murid terhadap penerapan model Problem Based Learning (PBL) menunjukkan respons yang sangat positif dengan persentase sebesar 94,17%, yang menandakan model pembelajaran ini dapat menarik, memotivasi, dan membantu murid dalam memahami materi pemisahan campuran. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model Problem Based Learning (PBL) efektif untuk meningkatkan keterampilan problem solving murid SMP.